Business And Government In Canada - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "Business and Government in Canada," by Stephen Brooks and Andrew Stritch.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Business government relations; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z